The Influence of Leadership Style and Motivation on The Performance of Teachers in Senior High School State and Private District Obi - Hamsin Alina; Ardin Umar (Peneliti.net, 2022)
The aims of this research are (i) to know leadership style and motivation about which one the most dominant influence variable of teachers’ performance in Senior High School State and Private District Obi Ternate. (ii) to know the most dominant influence between leadership style and motivation of teacher performance in Senior High School State and Private District Obi.This study used data collection technique by questionnaire. Total sample are 90 teachers. Data analysis used qualitative analysis to describe leadership variable deductive, participative leadership, democratic leadership, goal oriented leadership, motivation of teachers’ performance, qualitative analysis by multiple linier regression to know the influence between independent variable with dependent variable and hypothesis test with F test and T test respectively for simultaneous test and partial test. The result showed that variable with positive influence and significant with teachers’ performance in Senior High School State and Private District Obi are deductive leadership about 006 significant values, democratic leadership about 0,008 significant values and work motivation leadership about 0,002 significant values. Meanwhile the variable that has positive influence but doesn’t significant are participative leadership is 0,063 values and goal oriented leadership is 0,988. While the most dominant influence variable to teachers’ performance in Senior High School State and Private District Obi is motivation around 0,002 significant values.